The viability of human dental pulp cells and apical papilla cells after treatment with conventional calcium hydroxide and nanoparticulate calcium hydroxide at various concentrations - Kamolparn Pugdee; Awiruth Klaisiri; Panupat Phumpatrakom (Saudi Dental Journal)
Introduction: Nanoparticulate Ca(OH)2 had greater antibacterial effect than conventional Ca(OH)2. Conversely, a study reported that nanoparticulate Ca(OH)2 had toxicity against murine fibroblast. However, the study of nanoparticulate Ca(OH)2, involving human dental pulp cells (DPCs) and apical papilla cells (APCs) is lacking. The aim of this study is to compare the effects of conventional Ca(OH)2 and nanoparticulate Ca(OH)2 on the viability of DPCs and APCs. Methods: Primary human DPCs/APCs from the 3rd to 5th passage were divided into control and experimental groups. In the control group, cells were cultured in complete media. In the experimental group, cells were cultured in complete media containing 10, 100, or 1000 μg/mL of either conventional Ca(OH)2 or nanoparticulate Ca(OH)2 for 1, 3, 5, and 7 days. After the treatment period, the cells were tested for viability using MTT assay. Results: DPCs treated with conventional Ca(OH)2 in all concentrations at day 5 revealed significantly higher proliferation compared to nanoparticulate Ca(OH)2 treated groups. In additions, DPCs treated with 1000 µg/ml nanoparticulate Ca(OH)2 at day7 were significantly lower proliferation compared to DPCs treated with conventional Ca(OH)2. In contrast, APCs treated with 1000 µg/ml nanoparticulated Ca(OH)2 were significantly higher proliferation than APCs treated with 1000 µg/ml conventional Ca(OH)2 at day7. Conclusions: Nanoparticulate Ca(OH)2 increased the viability of APCs and can be an alternative choice of intracanal medication for regenerative endodontic procedures. However, Nanoparticulate Ca(OH)2 exerted some effects on DPCs. The use of nanoparticulate Ca(OH)2 has no advantages over the conventional Ca(OH)2 for vital pulp therapy.